2012
DOI: 10.3109/03639045.2012.662511
|View full text |Cite
|
Sign up to set email alerts
|

Quality investigation of hydroxyprogesterone caproate active pharmaceutical ingredient and injection

Abstract: The purpose of this study was to investigate the quality of hydroxyprogesterone caproate (HPC) active pharmaceutical ingredient (API) sources that may be used by compounding pharmacies, compared to the FDA-approved source of the API; and to investigate the quality of HPC injection samples obtained from compounding pharmacies in the US, compared to the FDA-approved product (Makena®). Samples of API were obtained from every source confirmed to be an original manufacturer of the drug for human use, which were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…[7,12–17] Because federal surveillance requirements do not exist for compounded drugs, the extent of quality and safety problems is unknown. [18]…”
Section: Compounded Drugs and Traditional Pharmacy Compoundingmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,12–17] Because federal surveillance requirements do not exist for compounded drugs, the extent of quality and safety problems is unknown. [18]…”
Section: Compounded Drugs and Traditional Pharmacy Compoundingmentioning
confidence: 99%
“…One additional sample of API labelled as hydroxyprogesterone caproate did not contain any active ingredient and was subsequently found to contain only glucose. [17]…”
Section: Compounded Drugs and Traditional Pharmacy Compoundingmentioning
confidence: 99%
“…A recent report by Chollet and Jozwiakowski from the Ther-Rx Corporation which markets Makena suggested that compounded 17-OHPC poses a risk as many unspecified impurities were identified in the active pharmaceutical ingredients (APIs) used to compound 17-OHPC and that the concentration of the compounded product was commonly not in the range of accepted potency 7 . The FDA conducted their own investigation and could not identify any major safety problems for compounded 17-OHPC.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Our purpose was to obtain compounded 17-OHPC formulations from compounding pharmacies throughout the United States and to analyze the product for potency (concentration), impurities, sterility and pyrogen status. Sterility and pyrogen status assessments of compounded 17-OHPC were not provided in the reports of the FDA or of Chollet and Jozwiakowski.…”
Section: Introductionmentioning
confidence: 99%
“…2 These investigators suggested that both the active pharmaceutical ingredient and compounded hydroxyprogesterone caproate products contained impurities that exceeded the bounds defined in the new drug application (NDA) submitted to FDA for hydroxyprogesterone caproate and claimed that 16% of analyzed samples of the compounded products containing hydroxyprogesterone caproate had impurities out of the NDA-specified range. However, it is unclear if deterioration of hydroxyprogesterone caproate contributed to these observations.…”
mentioning
confidence: 99%